Overview of scientific production in the use of mobile applications by hospital (Research, Society and Development, 2024)
The objective of this study was to identify the scientific production on the use of mobile applications with patient interface by hospital management. Method: integrative review of the literature carried out in the databases: Medical Literature and Retrivial System onLine (MEDLINE/PubMed®); Scientific Electronic Library Online (SciELO); Virtual Health Library (VHL). The PICo methodology was used to construct the research question and select the respective descriptors, including: “mobile applications”, “health communication”, “hospital administration”, “patients”. Five articles published between 2013 and 2023. Results: in the analyzes carried out on the functionality of the applications, all mobile applications in this study demonstrated managerial functionality, in addition to the communication interface with the patient through mobile applications. Conclusion: the present research offers theoretical and scientific-technological basis for the development of positive research on the use of technological management tools for communication between hospital management and patients, at the same time as they aim to minimize failures and variability in the processes that occur within the hospital.